1989
DOI: 10.1288/00005537-198906000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Surfer's ear in Japan

Abstract: Fifty-one Japanese professional surfers were examined in order to analyze surfer's ear. Forty-one cases (80%), 71 ears, were diagnosed as surfer's ear. In 19 cases (37%), 30 ears, the external auditory canals had stenosed by more than 50%. In general, surfer's ear begins to appear after 5 years and is further aggravated by continued surfing. The age at which surfing is taken up has no influence on the appearance of surfer's ear. Surfers who surf on northern (colder) coasts have severer surfer's ear than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
62
2
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 1 publication
12
62
2
5
Order By: Relevance
“…The percentage of exostosis in our cohort is comparable to the prevalence rates reported in other cold-water surfing areas in the world (Table I). [2][3][4][5][6][7][8] The occurrence of exostosis is thought to be related to cold-water exposure, although the exact pathogenesis is not clearly defined. A significant correlation between the duration of cold-water exposure and external auditory canal exostosis was demonstrated, which is in line with the widely accepted cold-water hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of exostosis in our cohort is comparable to the prevalence rates reported in other cold-water surfing areas in the world (Table I). [2][3][4][5][6][7][8] The occurrence of exostosis is thought to be related to cold-water exposure, although the exact pathogenesis is not clearly defined. A significant correlation between the duration of cold-water exposure and external auditory canal exostosis was demonstrated, which is in line with the widely accepted cold-water hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies of surfing communities in several countries have identified a higher prevalence of exostoses in populations exposed to colder waters. [3][4][5][6] This has led to many experts advocating the use of ear plugs or wetsuit hoods to prevent the ingress of cold water into the external auditory canal. Such precautionary measures should prevent the development and limit the progression of exostoses.…”
Section: Introductionmentioning
confidence: 99%
“…Auditory exostoses have also been observed in Neanderthals and some European Middle Pleistocene individuals excavated at Sima de los Huesos (Boule, 1911(Boule, -1913Trinkaus, 1983:70, 411;Pérez et al, 1997). Today, this trait is common in individuals who practice aquatic sports (Van Gilse, 1938;Adams, 1951;Dettman and Reuter, 1964;DiBartolomeo, 1979;Scrivener, 1981;Filipo et al, 1982;Kemink and Graham, 1982;Fabiani et al, 1984;Kennedy, 1986;Umeda et al, 1989;Deleyiannis et al, 1996;Kroon et al, 2002), and prevalence of auditory exostoses and degree of canal obstruction are positively correlated with intensity and number of years involved in aquatic sports (Fowler and Osmun, 1942;Umeda et al, 1989;Deleyiannis et al, 1996;Kroon et al, 2002;Altuna Mariezkurrena et al, 2004).…”
mentioning
confidence: 95%